A LOOK AT THE HISTORY OF PHRASEOLOGY - Halazdra, Svitlana; Pidvysotska, Galina (Sworld-Us Conference proceedings, 2023)
The article is focused on the main achievements of modern Ukrainian phraseology. The characteristic features of phraseological units, a number of classification systems and the place of the phraseologisms in the writer's language are given in the scientif